A statistical analysis of tackling performance during international Rugby Union matches from 2011 - van Rooyen, M. K. (International Journal of Performance Analysis in Sport, 2012)
The aims of this study were to i) investigate if playing position had any influence on tackle statistics and match outcome. ii) determine whether differences in tackle performance between the 6 Nations (n = 15), Tri Nations (n = 6) and Rugby World Cup (RWC) (n = 48) existed. Tackling and match related statistics were recorded (n = 69 matches) online from Verusco's Statistics Portal. Forwards (n = 8) made more tackles (66%) than Backs (n = 7) (34%), this was significant even when group size was accounted for. 'Missed' tackles were not different between the Forwards and Backs when group size was factored in. Winning team Forwards made a greater percentage of 'missed' tackles than losing teams Forwards. More tackles were observed during the 6 Nations (165 ± 28%) than either the Tri Nations (141 ± 24%) or RWC (156 ± 47%). Tackle completion rate was better for the 6 Nations (93 ± 3% vs. 87 ± 4.5% Tri Nations and 86 ± 5% RWC). The different effects that playing positions and styles had on tackling was highlighted. The most appropriate way to translate these findings back into rugby is through the development of more game related training exercises.